Genealogi Tarekat Neosufi di Indonesia: dari Ritual Eksklusif ke Aksi Sosial Kolektif - Budi Rahman Hakim; Fajrur Rahman (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2024)
This study examines the genealogical transformation of the Neosufi order in Indonesia, focusing on the shift from a private-ritual institution to an active and open social movement in the public space. Through a qualitative approach based on literature study and hermeneutic analysis, this paper highlights how the Qadiriyah Naqsyabandiyah Order (TQN) Suryalaya represents a new form of Sufism that combines spiritual depth with collective social action. This transformation is seen in various fields, ranging from drug rehabilitation, Islamic boarding school education, to spirituality-based economic empowerment. The order is no longer just a space for contemplation, but also plays a role in the process of social reconciliation, moral advocacy, and expansion into the public space through digital media. However, this dynamic also raises genealogical problems in the form of spiritual symbolization by the state, co-optation of power, and ambiguity in the interpretation of modernity. Indonesian Neosufism is a contextual response to spiritual and social crises, as well as a field of negotiation between the legacy of tradition, the demands of modernity, and the structure of state power. This study is a development of the author's dissertation and academic book manuscript that is being prepared for publication, thus presenting theoretical and practical contributions to the study of Sufism and social development.